Mejoramiento de la calidad de vida de la población escolar del tercer y cuarto año de educación básica de la escuela fiscal mixta “24 de Mayo” del barrio Pucacocha, parroquia el Valle, del cantón y provincia de Loja, mediante la atención básica bucodental, considerando su perfil epidemiológico. Período marzo septiembre del 2010 - Peralta Salazar, María Salomé (2010)
This research was carried out in the Joint Fiscal School "24 de Mayo" Pucacocha neighborhood, parish Valley, Canton and the Province of Loja, in the period from March to September 2010. Was conducted through the joint efforts of the investigator, supervisor, director of the school, teachers, parents, and students. The purpose was to determine the most prevalent of the / as school and intervene in them to improve the quality of life for students in third and fourth years of Basic Education School " 24 de Mayo”, through diagnosis and basic rehabilitation which was made through: the application of sealants, simple and complex dental surgery, pulp therapy (pulpotomy and pulpectomy), minor surgery, prophylaxis, fluoride application during the period, it was necessary to prepare the lifting of the profile schoolchildren's oral epidemiology, oral health education for children and parents and treatment of oral diseases as the major epidemiological profile. The target population was of 727 children belonging to different schools in the area of influx Hospital Universitario of Motupe Health Area No. 3. As the sample of thirty-nine children in the Third and Fourth Year Basic Education School Fiscal Mixed " 24 de Mayo", of which 15 were third year students parallel "B", and 24 fourth year students Basic Education, this sample was affected by the exclusion criteria. Once obtained the acceptance or rejection by parents, and the dropout of some children the final sample of 31 children who received basic dental restoration according to your needs, once the diagnosis corresponding to the modified clinical history of the Career of Dentistry Universidad of Loja the following results were obtained 16 children attended and 15 girls, ages 7 to 9 years. The ceod index in children is 5.4, and 5.3 in girls. As for the CPOD index is 2.6 in girls, whereas in children is 2.2. The disease with highest incidence of dental caries with alarming value of 100% in both boys and girls. As regards predisposing factors for the occurrence of oral diseases in children we have 7 years the accumulation of plaque and materia alba is 100% and the bad tooth position with a value of 66.6% in children aged 8 plate bacteria and tooth malposition is 100%, materia alba represents 37.5% in children aged 9 plaque and tooth malposition is 100% and 20% materia alba. In girls 7 years of plaque accumulation is 100%, materia alba and dental malposition was 75% in the age of 8 plaque is 100%, 83.3% materia alba and dental malposition the 50%, at the age of 9 years of plaque accumulation is 100%, dental malposition and materia alba is 80%. According to the study it was found that tooth decay is the disease prevalent in all ages followed by the predisposing factors such as the accumulation of bacterial plaque, materia alba and dental malposition, which was conducted by educational lectures on oral health to parents and students, can foster and educate the community about oral health care as an integral part of overall health.